The Leadership Style of the Madrasah Principal in Improving Teacher Performance at Mts Jailul Qur'an Wal Lughah Al-Asyari, Simpang Purwakarta - Ismail Baridi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the principal's leadership performance, the implementation of principal leadership in improving teacher performance, and the supporting and inhibiting factors as well as solutions to principal leadership at MTs Jailul Qur'an Wal Lughah Al-Asyari Simpang Purwakarta. The research employed a descriptive qualitative approach with data collected through in-depth interviews, participatory observation, and documentation. Informants included the principal, deputy principals, teachers, educational staff, and students. Data analysis used the Miles Huberman (2014) model comprising data reduction, data display, and conclusion drawing, with validity testing through source, time, and technique triangulation. The results indicate that: (1) The principal's leadership at MTs Jailul Qur'an Wal Lughah Al-Asyari is characterized by flexible democratic leadership, prioritizing deliberation, openness, and direct role modeling. (2) Leadership implementation is carried out through internal and external motivation, academic supervision, role modeling, and intensive interpersonal communication to improve teacher performance. (3) Supporting factors include the principal's commitment, a culture of deliberation, and teachers' collective enthusiasm; while inhibiting factors include limited infrastructure and varying teacher competencies, addressed through continuous training and internal coordination. This study concludes that the principal's democratic leadership significantly contributes to improved teacher performance, teaching motivation, and student achievement.